2014
DOI: 10.1007/s10620-014-3379-9
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine Promotes Intestinal Fibrosis in Rats with Trinitrobenzene Sulfonic Acid-Induced Colitis

Abstract: Hcy promotes intestinal fibrosis in rats with TNBS/ethanol-induced colitis, the underlying mechanisms of which may be attributed to its effects of increasing inflammatory damage, promoting the expression of profibrogenic cytokines and influencing MMPs/TIMPs balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The effects of homocysteine on the development of intestinal fibrosis were investigated in TNBS-induced rat model (Ding et al, 2015). Administration of homocysteine to rats with TNBS-induced colitis was found to aggravate the severity of intestinal inflammation with higher levels of TNF-α, IL-1β and IL-6.…”
Section: Involvement Of Mmps and Timps In Animal Models Of Intestinalmentioning
confidence: 99%
“…The effects of homocysteine on the development of intestinal fibrosis were investigated in TNBS-induced rat model (Ding et al, 2015). Administration of homocysteine to rats with TNBS-induced colitis was found to aggravate the severity of intestinal inflammation with higher levels of TNF-α, IL-1β and IL-6.…”
Section: Involvement Of Mmps and Timps In Animal Models Of Intestinalmentioning
confidence: 99%
“…The results suggested that homocysteine aggravated intestinal fibrosis in rats with TNBS/ethanol-induced colitis. The mechanisms were probably due to its effects on promoting the expression of profibrogenic cytokines and influencing the MMP/TIMP balance [48]. The possibility of the anti-fibrotic activity of HGF in the liver was indicated [49].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the increased expression of matrix metalloproteinase (MMP) and the decreased expression of tissue inhibitor of metalloproteinase (TIMP) and tight junction proteins (zonula occluden-1) indicate vascular remodelling. Hcy promots the expression of profibrogenic cytokines and influences the MMP/TIMP balance 40 . The MMP is known to regulate the activities of collagenase and gelatinase 41 .…”
Section: Discussionmentioning
confidence: 99%